Colorizing Ti-6Al-4V surface via high-throughput laser surface nanostructuring. (July 2019) - Wang, Qinghua; Samanta, Avik; Toor, Fatima; Shaw, Scott; Ding, Hongtao
Abstract: In this work, an innovative high-throughput laser surface nanostructuring process was developed to enhance the hydrophobicity and reduce the reflectivity of the Ti-6Al-4V surface using a nanosecond pulse laser. The laser textured Ti-6Al-4V surfaces exhibit combined anti-reflective, highly hydrophobic and mechanically enhanced effects. In the meantime, the anti-reflective Ti-6Al-4V surfaces show different colors when treated by different laser processing parameters. Compared with the existing ultra-short laser-based surface-texturing methods which often rely on the generation of micro-scale patterns using a focused laser spot and very fine spatial resolution, this innovative laser surface treatment method significantly increases the processing speed and reduces the production cost. This novel process will bring a new avenue for controlling the surface color, wettability and mechanical property of the important engineering surfaces.